Synthesis of Chebyshev Function Substrate Integrated Waveguide Filter - Chua, K.W. (Institute of Electrical and Electronics Engineers Inc., 2021)
In this paper, chained-response method is applied to the synthesis and design analysis of the substrate integrate waveguide (SIW) filters. SIW is smaller in size and offers low loss as well as high power handling just like the conventional waveguide filters. Chained-response multiband provides the flexibility in selecting inner-band frequency and the bandwidth for each of the passband. It is able to further improve the integration of wireless communication into a multiband system. From the simulation run in ANSYS HFSS, it is shown to have a good return loss performance of 13dB and an insertion loss of 1. 7dB, with a fractional bandwidth (FWB) of 3.5. A good agreement between the theoretical value and simulated value can be seen. Â© 2021 IEEE.